ANALISIS UNSUR WACANA LIRIK LAGU SHEILA ON 7 - , HASWIN FATKUROHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper contains the description of the results of elemental analysis of discourse lyrics Zero 7 (hereinafter referred to SO7). Elements of discourse in question is an internal element, the external elements, and theme of discourse. Elements of discourse SO7 song is one manifestation of real creativity creator speaking. The creativity of language indicated that led to a favorite song and have the impression for the audience. The things that make a song SO7 interesting to study, which is the creativity any language contained therein so as to make the audience favored and impressed. In addition, no studies have discussed the elements of discourse SO7 song lyrics. This research was done in three stages. First, the data collection phase using oral data are the lyrics of the song are spoken. The population of this study was overall SO7 song lyrics that are 85 songs from nine albums. Of the population to be sampled song number 31. Sampling was based on interviews with 37 informants were held on February 3 to 20. Second, the data analysis phase which uses the method match the method articulatory phonetic match. Third, the data analysis phase based discourse elements consisting of elements of internal, external elements, and theme of discourse. The results of the data analysis then presented with formal and informal methods. Elemental analysis showed internal use figurative language. a simile, personification, metonymy, epithet, and metaphor. The results of the analysis concluded that the internal elements that song lyrics have favored the use of figurative language is more dominant than the lyrics of the song are not favored. Analysis of the use of an external element to the identification of speech acts indicate that the lyrics of the song which has favored the main ideas contained in the title, the lyrics are the work of Eross. From this analysis it can be concluded that the initial part of the title is seen by a person to know the main ideas to be conveyed.Elemental analysis shows that the discourse theme song SO7 raised issues about love life, social, motivational, family, religious, friendship, unity, and loyalty. Based on the above, it can be concluded that the lovers lyrics like a beautiful language and themes of the lyrics of a song that is close to their daily lives.